2020
DOI: 10.1016/j.cell.2020.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Passenger Mutations in More Than 2,500 Cancer Genomes: Overall Molecular Functional Impact and Consequences

Abstract: Highlights d We characterize the passenger landscape in more than 2,500 whole-genome tumors d Molecular impact correlates with the mutational signature and subclonal architecture d The aggregated effect of passengers plays role in tumorigenesis beyond standard drivers d Additive-effects model from germline studies can be repurposed for cancer genomics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 62 publications
1
100
0
Order By: Relevance
“…However, several recent reports have showed that passenger mutations may also have critical functional roles in driving cancer, with some authors describing them as mini drivers. They found that the aggregated impact of putative passenger mutations could provide significant predictive power to distinguish cancer from non-cancer phenotypes (50,51). The above content implied to us that in some types of cancers, such as UCEC, even most of these mutations belonged to the unknown class; more efforts are needed to determine the meanings of these mutations, which might be found to also have important functional roles in driving tumorigenesis.…”
Section: Discussionmentioning
confidence: 98%
“…However, several recent reports have showed that passenger mutations may also have critical functional roles in driving cancer, with some authors describing them as mini drivers. They found that the aggregated impact of putative passenger mutations could provide significant predictive power to distinguish cancer from non-cancer phenotypes (50,51). The above content implied to us that in some types of cancers, such as UCEC, even most of these mutations belonged to the unknown class; more efforts are needed to determine the meanings of these mutations, which might be found to also have important functional roles in driving tumorigenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with this finding, most high VAF synonymous variants are not observed to co-occur with any candidate 'driver' mutation. The large number of unobserved 'drivers' likely include mCAs 10,11,29,30 , large structural variants 31,32 , coding mutations in non-cancer-associated genes, mutations in regulatory regions [33][34][35][36] and, possibly, epigenetic alterations 37,38 . We hypothesize that a more comprehensive survey of these alterations will yield many further mutations that will be shown to be capable of driving clonal expansions in blood 16 .…”
Section: Discussionmentioning
confidence: 99%
“…composer, era, genre). As a biological example, we show a mutational spectrum observed in a type of Kidney cancer, as adapted from [6]. As a musical example, we show the motif spectrum of three popular songs for comparison, where chord transitions have been normalized by the tonic chord.…”
Section: Extracting Musical Featuresmentioning
confidence: 99%
“…Particularly, in cancer genomics, the underlying processes that cause these mutations (e.g. tobacco, UV, aging, etc) can be directly linked with specific mutational signatures, and specific cancer types (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%